Investigation of students' academic participation in combined learning based on learning management system. - Daryadokht Masroor Roudsar; Haghani Hamid; Dehnad Afsaneh; Mojtaba Ghanbari Ghalesari; Shoub Ghasemi Maryam; Rokni Akbarian Mostafa (Medičnì Perspektivi)
Aim and Purpose – Using new methods and proper and interactive experiences can help improve the quality and attractiveness of education. The present study aimed to investigating the relationship between academic participation of nursing students who use combination education based on learning management system (LMS) and studied their degree of academic participation. This is a descriptive cross-sectional study in which the researcher has studied student participation through a demographic information form and a questionnaire on academic engagement. The purpose of this research was to study the nursing and midwifery faculty of Iran University of Medical Sciences in which 229 undergraduate nursing students were selected from the total of 280 from the second to the sixth semester by the total number and according to entry criteria. Then, data were analyzed by SPSS software version 23 and significance level less than 0.05, descriptive statistics, independent t-test, one way ANOVA, and Scheffe post hoc test and Pearson correlation. Most of the research units were female (52.8%), in the range of 21-29 years old (53.3%), single (90%) and native of Tehran (53.7%). The vast majority had a moderate or lower familiarity with the LMS system (75.5%). The majority did not easily access the LMS system (56.3%). Only 2.2% of the units had high satisfaction and 40.2% had relative satisfaction and 57.6% had low satisfaction from LMS-based combination training. The mean and standard deviation of the educational participation score was 51.16±14.86 and their behavioral subscale scores 69.68±16.48 and the emotional subscale was 49.56±20.53 and the cognitive subscale was 38.25±20.55%. According to the results of the study, most of the research units had low satisfaction with LMS-based combination training, which could increase student satisfaction by using all the capabilities of the learning management system and the more interactive design of the combination training, as the majority of previous studies have shown high satisfaction with combined training. Among the subscales of educational participation that have a positive relationship with academic success and academic achievement, the highest mean score was for subscales of behavioral participation and the lowest for cognitive subscales and this study did not show any relationship between the satisfaction of LMS-based combination education and the student's academic engagement.